STRATEGI EKSISTENSI KEPEMIMPINAN ADAT ULU APAD DESA TENGANAN PEGRINGSINGAN - Maheni, Pande Dwi Sinar; -, Bandiyah; Mahaswari Jayanthi, AA. Sg. Mirah (Jurnal Nawala Politika, 2021)
The purpose of this research is to know the leadership of adat ulu apad Tenganan Pegringsingan Village, especially related to the strategy developed by Indigenous villages to maintain the existence of indigenous leadership ulu apad. The study was framed using traditional and charismatic leadership theory by Max Weber. The research methods used descriptive methods with qualitative approaches. Respondents determind selected by purposive sampling. The result showed that a traditional leadership ulu apad is a leadership system based on the community marriage seniority. Leader in ulu apad have a traditional leadership types also have charismatic types. The existence of indigenous leadership ulu apad is maintained through of forming of cadre from an early age, which is socialization in their family and also materuna nyoman and medaha, that carried out over a one-year period in customary dormitories. Keywords : Ulu Apad, Tenganan Pengringsingan Village, forming of cadre, existence